PENGARUH PERSEPSI, PENGETAHUAN PERPAJAKAN, DAN PERTIMBANGAN PASAR KERJA TERHADAP MINAT BERKARIR DI BIDANG PERPAJAKAN (STUDI PADA MAHASISWA AKUNTANSI SEMESTER 5, 7 DAN ANGGOTA TAX CENTER UNIVERSITAS MAJALENGKA) - Aliyudin, Rizal Sukma; Eva Fauziah Ahmad; Robi Maulana Magribi; Sindi Rahayu (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
Supervision in the field of taxation is not yet optimal due to a lack of human resources involved in taxation. This creates job opportunities in the field of taxation, which can be utilized by accounting graduates. This phenomenon can be a chance for accounting graduates to pursue a career in taxation. The purpose of this study is to determine the influence of perception, taxation knowledge, and labor market considerations on career interest in taxation. The method used in this study is descriptive and verificative analysis. The population of this study is fifth and seventh-semester accounting students and the Tax Center of Majalengka University. The sample was determined using nonprobability sampling, using a saturated sampling method with 110 respondents. The results show that: (1) perception has a significant influence on career interest in taxation, (2) taxation knowledge has a significant influence on career interest in taxation, (3) labor market considerations have a significant influence on career interest in taxation, and (4) perception, taxation knowledge, and labor market considerations simultaneously influence career interest in taxation.